The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/genes14030553
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: A Cellular Guardian against Hepatic Lipotoxicity

Abstract: Lipotoxicity is a phenomenon of lipid-induced cellular injury in nonadipose tissue. Excess of free saturated fatty acids (SFAs) contributes to hepatic injury in nonalcoholic fatty liver disease (NAFLD), which has been growing at an unprecedented rate in recent years. SFAs and their derivatives such as ceramides and membrane phospholipids have been shown to induce intrahepatic oxidative damage and ER stress. Autophagy represents a cellular housekeeping mechanism to counter the perturbation in organelle function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 131 publications
0
4
0
1
Order By: Relevance
“…Our results showed that, indeed, similar to its effect on cellular viability, the targeted degradation of eRNA by RNase 1 significantly reduced the PA induced activation of JNK, its downstream target c-jun, and p38MAPK (Figure 1 E-J). Furthermore, Rnase 1 treatment also rescued PA induced autophagy block which is a major mediator of lipotoxicity [28] (Supplementary Figure 2). To verify if the observed effects of RNase 1 are specifically due to its effects on eRNA, we also used a pharmacological inhibitor of TLR3, a receptor of eRNA and observed a similar rescue effect on PA induced cell death (Figure 1K).…”
Section: Rnase 1 Attenuates Pa Induced Cellular Injury In Hepg2 Cellsmentioning
confidence: 88%
“…Our results showed that, indeed, similar to its effect on cellular viability, the targeted degradation of eRNA by RNase 1 significantly reduced the PA induced activation of JNK, its downstream target c-jun, and p38MAPK (Figure 1 E-J). Furthermore, Rnase 1 treatment also rescued PA induced autophagy block which is a major mediator of lipotoxicity [28] (Supplementary Figure 2). To verify if the observed effects of RNase 1 are specifically due to its effects on eRNA, we also used a pharmacological inhibitor of TLR3, a receptor of eRNA and observed a similar rescue effect on PA induced cell death (Figure 1K).…”
Section: Rnase 1 Attenuates Pa Induced Cellular Injury In Hepg2 Cellsmentioning
confidence: 88%
“…Notably, although RNase 1 restored p-JNK and p-p38MAPK back to the control levels, its effect did not restore p-c-JUN back to the control levels even though p-c-JUN levels were significantly rescued in RNase 1 and PA-treated cells. Furthermore, the RNase 1 treatment also rescued PA-induced autophagy block, which is a major mediator of lipotoxicity [29] (Supplementary Figure S2). To verify if the observed effects of RNase 1 are specifically due to its effects on eRNA, we also used a pharmacological inhibitor of TLR3, which is a receptor of eRNA, and observed a similar rescue effect on PA-induced cell death (Figure 1L).…”
Section: Rnase 1 Attenuates Pa-induced Cellular Injury In Hepg2 Cellsmentioning
confidence: 88%
“…Відомо препарати, які використовуються в сучасній фармакотерапії, можуть індукувати або пригнічувати протікання (тривалість) аутофагії [57]. Є дані про цільовий вплив на аутофагію (стимуляція і пригнічення) за певних захворювань легень, печінки, нейродегенеративних та інфекційних хвороб [58][59][60][61][62][63].…”
Section: цільовий вплив на аутофагію в умовах різних захворюваньunclassified